The factors that affect employee’s performance / Shafaah Sharif - Sharif, Shafaah (Faculty of Business and Management, 2018)
Employees are among an organization’s most important resources and the most valuable assets. Thus it involves several factors that affect it. Training, rewards, working environment and leadership are the factors that affect employee’s performance in an organization. This study emphasizes on the relationship between training, rewards, working environment and leadership styles towards employee’s performance in FELCRA Berhad Wilayah Tengah. The research study is design based on a quantitative approach. Not only that, descriptive and explanatory analysis is applied in this research study. Characteristics of the population can be described through descriptive analysis. Meanwhile, the explanatory analysis is used to establish a relationship between variables. The questionnaire will be distributed and collected to obtain the result of this research paper. The results are based on the key data by SPSS program. This program would be explained in detail using the correlation to test whether there is a relationship between dependent variable and independent variable. The purpose of this chapter is to tabulate and analyses data in a meaningful and precise manner. The data was run using the software of SPSS and the result will be explained in detail in this chapter. The data used in the research is taken from the structured questionnaire obtained from employees of FELCRA Berhad Wilayah Tengah.